Pengaruh Massage Effleurage Menggunakan Minyak Jahe Terhadap Intensitas Nyeri Punggung Bawah Pada Penenun di Kelompok Putri Mas Desa Batuagung - Putu Diah Maharani Diah Maharani; Ni Rai Sintya Agustini; Dwi Prima Hanis Kusumaningtiyas (POLTEKKES KEMENKES YOGYAKARTA, 2025)
Introduction: Lower Back Pain (LBP) is a discomfort condition commonly experienced by individuals, especially weavers, causing muscle stiffness and soreness. If not treated properly, this condition may reduce their productivity. This study uses a non-pharmacological approach by examining the effect of effleurage massage with ginger oil on the intensity of low back pain among the Putri Mas group in Batuagung Village. Methods: The study used a pre-experimental design with a one group pre-test dan post-test approach. The population consisted of weavers from Putri Mas Group in Batuagung Village. A total of 53 respondent were selected using purposive sampling. The intervention was given by massaging the respondent’s back using effleurage technique with ginger oil for 15 minutes per session. Pain intensity before and after the intervention was measured using the Numeric Rating Scale (NRS). The data were analyzed using the Wilcoxon Signed Rank Test. Results: Before the therapy, all weaver experienced lower back pain, mostly in the moderate pain category. After the intervention, all weaver showed a decrease in pain intensity with most of them in the mild pain category. The Wilcoxon Signed Rank Test showed a Z value of -6,783 with a p-value <0,001, which means the result is significant (p < 0,05). Therefore, the null hypothesis was rejected and the alternative hypothesis was accepted. Discussion: The result showed that effleurage massage using ginger oil had an effect in reducing lower back pain intensity in weavers. Future studies are recommended to include a control group and a larger sample across weaving groups Keyword: Effleurage massage, ginger oil, lower back pain, non-pharmacological therapy